Seminar Report FOSI-IAS-SEPM Regional Seminar: Past and Present Sedimentation in Tropical Region - Barry Majeed Hartono; Ahmad Najili (Ikatan Ahli Geologi Indonesia, 2019)
Tropical sedimentations are unique. The “unique” term that given for tropical sedimentation is because that this sedimentation is affected by climates, vegetation, and high rate of weathering. The understanding of recent and modern tropical sedimentation can be used to study the sedimentation happened in the past. So studies about tropical sedimentation hopefully could help and improve the understanding of oil and gas exploration or coal exploration.FOSI 3rd Regional Seminar was held first September in Grha Sabha Pramana (UGM Conference Centre) Yogyakarta, Indonesia. Indonesian Sedimentologist Forum (FOSI) together with International Sedimentologist Association (IAS) and Society of Sedimentary Geology (SEPM) organized the joint Seminar. This Seminar was held also as a follow up from lecture (FOSI special meeting) in 2016 that was given by Prof. Poppe de Boer (Utrecht University) and Ir. Herman Darman (FOSI) in Gadjah Mada University (UGM).